2017
DOI: 10.1038/s41598-017-10156-w
|View full text |Cite
|
Sign up to set email alerts
|

Predicting the Ionic Product of Water

Abstract: We present a first-principles calculation and mechanistic characterization of the ion product of liquid water (K W), based on Quantum Cluster Equilibrium (QCE) theory with a variety of ab initio and density functional methods. The QCE method is based on T-dependent Boltzmann weighting of different-sized clusters and consequently enables the observation of thermodynamically less favored and therefore low populated species such as hydronium and hydroxide ions in water. We find that common quantum chemical method… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
47
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7
1

Relationship

6
2

Authors

Journals

citations
Cited by 47 publications
(51 citation statements)
references
References 66 publications
(58 reference statements)
1
47
0
Order By: Relevance
“…In the context of water magnetization, the principle imparts the following attributes to the parameters as represented in Eqs. ( 4 ) and ( 5 ), respectively [ 31 ]. Water molecules ionize to form H + and OH − ions under equilibrium condition based on Eq.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the context of water magnetization, the principle imparts the following attributes to the parameters as represented in Eqs. ( 4 ) and ( 5 ), respectively [ 31 ]. Water molecules ionize to form H + and OH − ions under equilibrium condition based on Eq.…”
Section: Resultsmentioning
confidence: 99%
“…In the context of water magnetization, the principle imparts the following attributes to the parameters as represented in Eqs. (4) and (5), respectively [31].…”
Section: Correlation Of Ph and Orp Calculationsmentioning
confidence: 99%
“…With 1.0 % water concentration, the average domain size increases to two molecules which indicates the appearance of small clusters. It has been shown that water clusters of small size form homodromic structures depending on their state [84,85] . If the concentration of water is further increased, the clusters become bigger and increasingly dominating.…”
Section: Resultsmentioning
confidence: 99%
“…Applications of the QCE method involve many neat and binary systems, including water, [4,67,68] aqueous solutions [15,69] and even ionic liquids. [70] In addition, we calculated activity coefficients [71] and ionicity [17,18,72] with binary QCE and we applied QCE or cluster weighting CW to vibrational circular dichroism [7] .…”
Section: The Cluster-weighting Methodsmentioning
confidence: 99%